Recurrence beyond the Milan criteria after curative‐intent resection of hepatocellular carcinoma: A novel tumor‐burden based prediction model. Issue 5 (29th June 2020) - Tsilimigras, Diamantis I.; Mehta, Rittal; Guglielmi, Alfredo; Ratti, Francesca; Marques, Hugo P.; Soubrane, Olivier; Lam, Vincent; Poultsides, George A.; Popescu, Irinel; Alexandrescu, Sorin; Martel, Guillaume; Hugh, Tom; et al.
Abstract: Background: Accurate prediction of recurrence patterns of hepatocellular carcinoma (HCC) may allow for prioritization of patients for resection or transplantation as well as guide post‐resection surveillance strategies. Methods: Patients who underwent curative‐intent R0 resection for HCC between 2000 and 2017 were identified using a multi‐institutional database. A prognostic model that incorporated HCC tumor burden score (TBS) to predict recurrence beyond the Milan criteria (MC) was developed and validated. Results: Among 718 patients who underwent R0 resection for HCC, 185 (25.8%) recurred within and 110 (15.3%) beyond the MC. On multivariable analysis, AFP more than 400 ng/mL (hazard ratio [HR] = 2.26; 95% confidence interval [CI]: 1.27‐4.02), lymphovascular invasion (HR = 2.00; 95% CI: 1.14‐3.50), and TBS (HR = 1.08; 95% CI: 1.03‐1.12) were associated with recurrence beyond the MC. A weighted TBS‐based score was constructed: [0.074*TBS + 0.692*lymphovascular invasion (yes: 1, no: 0) + 0.816*AFP > 400 (yes:1, no:0)]. Patients with a low, medium, and high TBS‐based risk score had a 5‐year incidence of recurring beyond the MC of 16.2%, 28.6%, and 47.2%, respectively ( P < .001). The predictive accuracy of the model was very good in the training (C‐index: 0.761) and validation (C‐index: 0.706) datasets and outperformed the previously reported clinical risk score (CRS; C‐index: 0.680). Conclusion: A TBS‐based model accurately predicted recurrence beyond MC after curative‐intent resection of HCC and outperformed the CRS. Incorporating TBS allows for better risk stratification and identifies patients in need of closer surveillance.